$\displaystyle (x^2)(y+1)dx + (y^2)(x-1)dy = 0$

1) it's not exact, I know that

2) I tried turning it into an exact equation using Euler's multiplicating factor (not sure this is the right word in English), but couldn't find the factor

3) tried the y/x=v substitution and ended up with:

xv + 1 + xv^3 - v^3 + x^2v^2v' - xv^2v' = 0

and I've no idea how to separate the x and v here

4) tried separating the variables and ended up with this:

$\displaystyle \frac{(x-1)^2}{2} + 2(x-1) +ln|x-1| + \frac{(y+1)^2}{2} - 2(y+1) + ln|y+1| = C$

what do I do?

thanks.